If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + -7 = -32 Reorder the terms: -7 + 5a = -32 Solving -7 + 5a = -32 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 5a = -32 + 7 Combine like terms: -7 + 7 = 0 0 + 5a = -32 + 7 5a = -32 + 7 Combine like terms: -32 + 7 = -25 5a = -25 Divide each side by '5'. a = -5 Simplifying a = -5
| 3x+2=7x+14 | | 3x+2+7x=14 | | 11-4x=75 | | 3p+15=60-2p | | 3p+15=80-2p | | 54-7x=2x+22 | | 9-10x=34-17x | | 127-2x=6x+7 | | 3+7x=69+x | | 2x+21=12x-59 | | 9x-27=3x+3 | | 10x-14=66 | | 3x-2y=7 | | 3+2x+(3x-4)=2x+12-(x-7) | | 2*8+5*3= | | 4x+0.28=0.22x | | 2x-0.22=5x+3 | | 2x-2.3=5x+3 | | Ln(2x+1)+ln(3x-5)=1 | | (-7t^3)(5t^8)= | | (4x^3-2)(5x^2-1)= | | -6x^2(8x^3-7x-4)= | | (9x^3-6x^2-11x-4)-(4x^3-8x^2-13x+5)= | | 7x-5=2x | | 5x+12=2x | | 20x+15x=20 | | x+3x=9.20 | | 6x-3y+7=-6x+2y-3 | | 3x+36=7x | | 5x+1=3x+9 | | 2c^2=h | | 6x-7=2x+21 |